2006
DOI: 10.1152/ajpendo.00363.2005
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of IGF system components in proliferating vs. differentiating growth plate chondrocytes: the functional role of IGFBP-5

Abstract: Kiepe, Daniela, Sonia Ciarmatori, Anke Haarmann, and Burkhard Tönshoff. Differential expression of IGF system components in proliferating vs. differentiating growth plate chondrocytes: the functional role of IGFBP-5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…Quite strikingly, OA chondrocytes were particularly well responsive to the treatment by rAAV IGF-I here, in marked contrast with their otherwise established hyporesponsiveness to the growth factor (59,72). Of note, we also observed that IGF-I overexpression in OA cartilage in situ was capable of significantly decreasing the expression of IGFBP3 and IGFBP4, two inhibitors of the IGF-I actions (40)(41)(42), while increasing the levels of two of its potentiators (IGFBP5 and its own receptor [IGF-IR]) (42,43), an effect noted at prolonged time points and probably the result of the steady levels of IGF-I production from the rAAV transgene sequence. In this regard, the effects of IGF-I on these components of the IGF-I axis via rAAV in OA cartilage are in good agreement with previous findings when providing IGF-I as a recombinant molecule to articular chondrocytes in vitro (73)(74)(75)(76).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Quite strikingly, OA chondrocytes were particularly well responsive to the treatment by rAAV IGF-I here, in marked contrast with their otherwise established hyporesponsiveness to the growth factor (59,72). Of note, we also observed that IGF-I overexpression in OA cartilage in situ was capable of significantly decreasing the expression of IGFBP3 and IGFBP4, two inhibitors of the IGF-I actions (40)(41)(42), while increasing the levels of two of its potentiators (IGFBP5 and its own receptor [IGF-IR]) (42,43), an effect noted at prolonged time points and probably the result of the steady levels of IGF-I production from the rAAV transgene sequence. In this regard, the effects of IGF-I on these components of the IGF-I axis via rAAV in OA cartilage are in good agreement with previous findings when providing IGF-I as a recombinant molecule to articular chondrocytes in vitro (73)(74)(75)(76).…”
Section: Discussionmentioning
confidence: 77%
“…We also analyzed the extent by which the candidate treatment with the rAAV-human IGF-I (rAAV-hIGF-I) vector was capable of durably restoring the structure of human OA cartilage vis-à-vis normal cartilage. Finally, we investigated the influence of rAAV-mediated IGF-I production upon the expression of key effectors of the IGF-I axis, specifically the IGF-binding proteins 3, 4 and 5 (IGFBP-3 to IGFBP-5) as well as the IGF-I receptor (IGF-IR) and downstream mitogenactivated protein kinase/extracellular signal-regulated kinase 1/2 (MAPK/ERK-1/2) and phosphatidylinisitol-3/Akt (PI3K/Akt) signal transduction pathways (33)(34)(35)(36)(37)(38)(39), reported as being inhibitors (IGFBP3 and IGFBP4) (40)(41)(42) or potentiators (IGFBP5 and IGF-IR) (42,43) of the IGF-I actions during OA pathogenesis.…”
Section: Benefits Of Recombinant Adeno-associated Virus (Raav)-mediatmentioning
confidence: 99%
“…In this regard, it is known that IGFBP-5 potentiated IGF-I actions on chondrocyte differentiation (21). Furthermore, it has also been shown that IGF-I stimulates IGFBP-5 expression in chondrocytes (22).…”
Section: Discussionmentioning
confidence: 98%
“…The software provided from the company allowed the quantitative detection of fluorescence by the incorporation of the substance SyberGreen into the amplification products. Amplification was performed in the presence of Universal Mastermix (PE Applied Biosystems) with SyberGreen to detect PCR products at the end of each amplification step, and the results were analyzed as already reported (Kiepe et al 2006).…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
“…For total cell homogenate cells were incubated with the indicated substances, scraped in 50 ml ice-cold lysis buffer containing a mixture of proteinase and phosphatase inhibitors, and cell extracts were treated as reported previously (Hömme et al 2003, Kiepe et al 2006. Cytosol membrane and nuclear factions of cells were prepared by previously described procedures (Hoeflich et al 2004).…”
Section: Western Immunoblottingmentioning
confidence: 99%